Nonstationary relationship between sea ice over Kara–Laptev seas during August–September and Ural blocking in the following winter. (1st September 2020) - Wang, Sai; Nath, Debashis; Chen, Wen
Abstract: In the current manuscript, we investigate the relationship between sea‐ice extent (August–September) over Kara–Laptev Seas (SIEKL) and the variability of Ural blocking in the following winter months (December–February, DJF). It is found that the linkage between SIEKL and Ural blocking in the following winter arises partly due to the influence of barotropic teleconnection pattern, emanated from the east coast of North America. The teleconnection can influence the mean Kara–Laptev sea ice variability during August–September. The memory of this teleconnection in the sea surface temperature (SST) anomalies over the North Atlantic Ocean further influences the Ural blocking in the following winter. The relationship between the SIEKL and Ural blocking has experienced a significant interdecadal change around mid‐1990s. The SIEKL‐related positive geopotential height anomalies over the Ural Mountains in the following winter are stronger during 1979–1996 period compare to the 1997–2017 periods. The differences in geopotential height anomalies between the two periods are related to the differences in the strength of synoptic‐scale eddy feedback. The feedback is stronger in the earlier period, which is conductive to the maintenance and amplification of positive geopotential height anomalies over the Ural Mountains, whereas the feedback is weaker in the later period. Further analysis suggests that the weakening of synoptic‐scale eddy feedback is due to weakening in the intensity of wintertime synoptic‐scale eddy activity on an interdecadal scale over the Barents Sea and northern Siberian sector. Abstract : The image shows the climatology of winter mean blocking frequency during 1981‐2010. The blocking frequency is higher over the Ural Mountains and stretches from northeastward to Far East at higher latitudes. The high frequency of occurrences maximize within the region between 52.5°N‐72.5°N and 30°E‐90°E. The Sea Ice Concentration anomalies during August‐September show high coherence with winter mean blocking index. The relationship between the Arctic sea ice and wintertime Ural blocking is essential to calculate the sea ice index.